2007
DOI: 10.1016/j.gca.2006.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Two cation exchange models for direct and inverse modelling of solution major cation composition in equilibrium with illite surfaces

Abstract: Na/K, Na/Ca and Na/Mg exchange isotherms were performed on the fine fraction (<2 lm) of Imt-2 illite samples at a total normality of about 0.005 mol/L in anionic chloride medium. The derived selectivity coefficients for Na/K, Na/Ca and Na/Mg were found to vary as a function of the exchanger composition and compared well with the data collected in the literature for similar experimental conditions. Two models were built to reproduce the data: the first was a multi(2)-site model with constant Gaines and Thomas s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 30 publications
3
28
0
Order By: Relevance
“…The model considers ion exchange on illite and smectite represented by the selectivity exchange coefficients on the two exchangers [42,43].…”
Section: Callovian-oxfordian Claystone Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The model considers ion exchange on illite and smectite represented by the selectivity exchange coefficients on the two exchangers [42,43].…”
Section: Callovian-oxfordian Claystone Modelmentioning
confidence: 99%
“…The ion exchange composition on the claystone was initially equilibrated with the COx pore water shown in Table 4. The selectivity coefficients available in Table 9 were calculated using exchange models given by Tournassat et al [42,43]. The coefficients are based on the Gaines and Thomas convention [50,51].…”
Section: Ion Exchangementioning
confidence: 99%
“…Analyses of cation exchange populations were performed on whole rock samples using the cobalt hexamine method (Rémy and Orsini, 1976;Ciesielski and Sterckeman, 1997) as previously described by Gaucher et al (2004Gaucher et al ( , 2006 and Tournassat et al (2007Tournassat et al ( , 2008Tournassat et al ( , 2009. Experimental tests showed that carbonate minerals and sulphate minerals (e.g.…”
Section: Determinations Of Cation Exchange Populations and Cation Excmentioning
confidence: 99%
“…Cation concentrations in the supernatant and in the cobalt hexamine solutions were analysed by liquid ionic chromatography (HPLC, Dionex). Cation exchange selectivity coefficients were calculated from these data (see Tournassat et al, 2007 for method details).…”
Section: Determinations Of Cation Exchange Populations and Cation Excmentioning
confidence: 99%
“…It is not a thermodynamic constant, but varies with the exchanger composition (e.g. Tournassat et al, 2007after Jensen, 1973. For the exchanger phases of the three sediment types (sand, sand with kankar, kankar), equilibrium equations for Na/K, Na/Mg, Na/Ca, Na/NH 4 were set up using the Gaines Thomas convention (Gaines & Thomas, 1953) and measurements of the cation compositions on the exchanger as well as the corresponding activities in groundwater samples.…”
Section: Tools and Modelling Strategymentioning
confidence: 99%